Salt reduction in bread via enrichment of dietary fiber containing sodium and calcium. Issue 6 (2nd March 2021) - Li, Yan-Lei; Han, Kai-Ning; Feng, Guang-Xin; Wan, Zhi-Li; Wang, Gao-Shang; Yang, Xiao-Quan
Abstract : A novel salt reduction strategy in bread via the enrichment of dietary fiber-contained sodium and calcium. Abstract : The high intake of sodium and low intake of dietary fiber are two major dietary risk factors for preventable deaths worldwide, highlighting the need and implementations for developing health foods with low-salt/high-dietary fibers. Bread as a staple food contributes about 25% to the daily intake of sodium in many countries, and salt reduction in bread still remains a great technical challenge. In this study, we developed a simple method to reformulate the white bread in terms of reducing salt contents via dietary fiber fortification, while maintaining the taste and texture qualities. Low molecular weight water-extractable arabinoxylans (LMW-WEAX) as a soluble dietary fiber was first hydrated in salt water before dough mixing, leading to an inhomogeneous spatial distribution of sodium in bread and accelerating the release of sodium ions from crumbs, allowing 20% salt reduction in bread without impacting the salt perception. Data from the moisture content, crumb structure, water distribution, dough rheology and bread texture properties suggest that the pre-hydrated incorporation of LMW-WEAX mitigates the detrimental effect of dietary fiber on the dough and bread quality. The modulation of Ca 2+ on the permeability of Na + through the mucus layer and implication in salt enhancement of the bread were investigated. Results show that the pre-hydrated incorporation of WEAX containing Na + and Ca 2+ (1.0%) makes it possible to reduce 30% salt content in breads, which have implications in the large-scale production of low-salt/high-dietary fiber bread.